2002
DOI: 10.1074/jbc.m103939200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Clostridium perfringensIota-Toxin with Lipid Bilayer Membranes

Abstract: The interaction between model lipid membranes and the binding component (Ib) of the ADP-ribosylating iotatoxin of Clostridium perfringens was studied in detail. Ib had to be activated by trypsin to result in channel formation in artificial lipid bilayers. The channels formed readily by Ib had a small single-channel conductance of about 85 picosiemens in 1 M KCl. Channel function was blocked in single-channel and multichannel experiments by the enzymatic component Ia in a pH-dependent manner. The strong Ia-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 48 publications
4
85
0
Order By: Relevance
“…Following the separation of Ia and Ibp from early-log-phase (Ͻ10-h) cultures of C. perfringens type E, as done by DEAE ion-exchange chromatography, trypsin proteolysis of fractions containing Ibp or Ia markedly (i) increases enzymelinked immunosorbent assay (ELISA) readings for Ibp, but not Ia, versus the same untreated fractions, thus suggesting a conformational shift in Ibp that unveils cryptic epitopes recognized by Ib-specific antibodies; and (ii) increases the guinea pig dermonecrotic activity of the Ibp fraction when combined with untreated Ia. It was subsequently discovered, after cloning and sequencing of the -toxin gene, that proteolytic activation of Ibp into Ib occurs at A211 (323), which then facilitates Ia docking (419), formation of voltage-dependent ion-permeable channels in membranes (213), and formation of SDS-stable heptamers on cell membranes (288,420) and in solution (49,288). However, Ib oligomers formed in solution are seemingly less stable and do not promote cytotoxicity compared to solution-generated oligomers of PA63 or C2IIa.…”
Section: Perfringens Ibp and Iamentioning
confidence: 99%
“…Following the separation of Ia and Ibp from early-log-phase (Ͻ10-h) cultures of C. perfringens type E, as done by DEAE ion-exchange chromatography, trypsin proteolysis of fractions containing Ibp or Ia markedly (i) increases enzymelinked immunosorbent assay (ELISA) readings for Ibp, but not Ia, versus the same untreated fractions, thus suggesting a conformational shift in Ibp that unveils cryptic epitopes recognized by Ib-specific antibodies; and (ii) increases the guinea pig dermonecrotic activity of the Ibp fraction when combined with untreated Ia. It was subsequently discovered, after cloning and sequencing of the -toxin gene, that proteolytic activation of Ibp into Ib occurs at A211 (323), which then facilitates Ia docking (419), formation of voltage-dependent ion-permeable channels in membranes (213), and formation of SDS-stable heptamers on cell membranes (288,420) and in solution (49,288). However, Ib oligomers formed in solution are seemingly less stable and do not promote cytotoxicity compared to solution-generated oligomers of PA63 or C2IIa.…”
Section: Perfringens Ibp and Iamentioning
confidence: 99%
“…It was shown for anthrax toxin (29) as well as for the family of actin-ADP-ribosylating toxins (10,30,31) that the binding components form pores in artificial lipid membranes. These pores were proposed to interact with the enzyme components (31,32) and to be involved in their translocation. Moreover, it was reported that anthrax lethal factor (LF) must be unfolded for translocation (19), and we have obtained similar results for C2I.…”
Section: Fig 7 Influence Of Bafilomycin A1 or Hsp90 Inhibitorsmentioning
confidence: 99%
“…However, we have no direct evidence that C2I translocates via the lumen of the pore across the membrane. Recently, Knapp et al showed that Ib, the binding component of C. perfringens iota toxin and another member of the family of binary actin-ADP-ribosylating toxins, forms pores in black lipid bilayer membranes and that these pores are partially "closed" by the enzyme component Ia (29).…”
Section: Fig 6 Ph-dependent C2i Translocation Into the Cytosol Of Vmentioning
confidence: 99%